AN ANALYSIS OF MORAL DEVELOPMENT OF NIM ROUSE'S CHARACTER IN NIM'S ISLAND FILM - Silalahi, Selvy Risma Asmianty; Kuncara, Singgih Daru; Wati, Erna (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2018)
ABSTRACTChildren’s literature is considered as one of the most prominent doorways for children to experience and expose the real world. Its influence on the child’s development and shaping of ideologies has been brought to the attention of many intellectuals and educationalists. Therefore, the researcher analyzed a main character’s moral development in this study. Moral development is important in children’s literature, where stories do not only focus on bizarre events, but, also on the individual personalities. The researcher analyzed the main character in the Nim’s island film, because the main character, Nim Rouse, was the only child who lived in an isolated island. The researcher used three different theories: the character identification by Jacob, moral development by Kohlberg, and cognitive theory by Piaget to analyze Nim Rouse character. These three theories helped the researcher in analyzing Nim Rouse’s moral and character development. This study showed that of all the six stages in Kohlberg’s moral development, Nim Rouse character only got through the first to the third stage due to the condition of the fourth to the sixth stage that only for the children who are having the social interaction with the outside world, which for Nim Rouse, she lived in an isolated island. Even so, the researcher saw that Nim Rouse character having well moral growth and development. She was able to develop emotions such as love, attention, and compassion for others.Keywords: Children’s Literature, Character Identification, Moral Development, Cognitive, Character Development  ABSTRAKSastra anak merupakan salah satu media yang paling penting dan populer bagi anak-anak dalam mengalami dan menjelajahi dunia nyata. Pengaruh sastra anak itu sendiri dalam perkembangan anak dan pembentukan ideologi mereka telah diteliti sekian lama oleh para intelektual dan pendidik. Oleh karenanya, penulis menganalisa perkembangan moral dari seorang karakter utama dalam studi ini. Mengingat perkembangan moral sangatlah penting dalam sastra anak, dimana cerita-ceritanya tidak hanya berfokus pada peristiwa-peristiwa menakjubkan tetapi juga pada sikap-sikap para individunya. Penulis menganalisa karakter utama difilm Nim’s Island bernama Nim Rouse, seorang anak yang tinggal di pulau terpencil. Penulis menggunakan teori identifikasi karakter Jacob, teori perkembangan moral Kohlberg, dan kognitif teori dari Piaget untuk menganalisa karakter Nim Rouse. Ketiga teori ini membantu penulis dalam menganalisa perkembangan moral Nim Rouse dan perkembangan karakter Nim Rouse itu sendiri. Studi ini menunjukkan bahwa dari keenam tingkatan perkembangan moral Kohlberg, karakter Nim Rouse hanya mengalami perkembangan moral dari tingkatan 1 sampai 3, dikarenakan tingkatan 4 sampai 6 hanya bisa dilewati bagi anak-anak yang mengalami interaksi sosial dengan dunia luar, sedangkan pada kasus Nim Rouse, ia hidup di pulau terpencil. Meskipun begitu, penulis melihat bahwa Nim Rouse mengalami pertumbuhan dan perkembangan moral yang baik. Ia mampu mengembangkan emosi-emosi seperti kasih sayang, perhatian, dan simpati terhadap orang lain. Kata Kunci: Sastra Anak, Identifikasi Karakter, Perkembangan Moral, Kognitif, Perkembangan Karakter